2009
DOI: 10.1002/cncr.24148
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study of cetuximab in combination with docetaxel in chemotherapy‐refractory/resistant patients with advanced nonsmall cell lung cancer

Abstract: Background Cetuximab in combination with docetaxel was examined in chemotherapy-refractory/resistant patients with advanced nonsmall-cell lung cancer (NSCLC) to determine response rate, survival, safety, and pharmacokinetics (PK). Methods Patients had evidence of epidermal growth factor receptor (EGFR) expression (≥1 +) and tumor progression during or disease recurrence within 3 months after chemotherapy. Cetuximab was administered weekly (400 mg/m2 initial; 250 mg/m2 thereafter). Docetaxel was administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…21 In addition, other trials preliminarily showed that either cetuximab combined with carboplatin and taxane or cetuximab combined with gemcitabine produced modestly clinical benefit. [22][23][24][25][26][27] Most target therapeutics show superiority just in a subset of patients (the preponderant population) and the preselection of patients becomes a key factor in the clinical setting. 28 So, it is necessary to find the preponderant population among NSCLC for the combination of cetuximab and DDP, just as the ones with wild type of K-ras gene among mCRC for the combination of cetuximab and CPT-11.…”
Section: Resultsmentioning
confidence: 99%
“…21 In addition, other trials preliminarily showed that either cetuximab combined with carboplatin and taxane or cetuximab combined with gemcitabine produced modestly clinical benefit. [22][23][24][25][26][27] Most target therapeutics show superiority just in a subset of patients (the preponderant population) and the preselection of patients becomes a key factor in the clinical setting. 28 So, it is necessary to find the preponderant population among NSCLC for the combination of cetuximab and DDP, just as the ones with wild type of K-ras gene among mCRC for the combination of cetuximab and CPT-11.…”
Section: Resultsmentioning
confidence: 99%
“…Cetuximab, a humanised monoclonal antibody that prevents ligand binding to the extracellular domain of EGFR, has shown encouraging results in NSCLC in combination with standard chemotherapy, in both the first-and second-line settings [79][80][81][82][83]. In the First-Line ErbituX in Lung Cancer (FLEX) study, a randomised, phase III study of cetuximab combined with cisplatin/vinorelbine (CV) versus CV alone in the first-line treatment of patients with EGFR immunohistochemistry (IHC)-positive advanced NSCLC, patients receiving cetuximab had statistically longer OS (primary end-point) than those receiving CV alone (11.3 versus 10.1 months; HR 0.871; p50.044).…”
Section: Antibodies To Egfr In Nsclc: Waiting For a Predictive Biomarmentioning
confidence: 99%
“…Cetuximab was investigated in pretreated NSCLCs in a phase II trial in addition to docetaxel 75 mg/m 2 in patients who had progressed on prior platinum chemotherapy; a median survival time of 7.5 months was reported and a 28% response rate. 35 A phase II trial was conducted with cetiximab as monotherapy in pretreated NSCLCs, with a median survival of 8.1 months and 1 year survival of 41%. 36 Cetuximab's use as a first line therapy was investigated in three phase II trials, in addition to platinum-containing chemotherapy, as first line treatment in EGFR mutation positive patients.…”
Section: Pharmacology and Pharmacokineticsmentioning
confidence: 99%